Inovações tecnológicas e novas formas de proteção aos direitos autorais na indústria fonográfica - Toyama, Míriam Costa (2006)
This dissertation tries to analyze the impact of a recent set of innovation connected to Internet and to digital technology. This technologies seems to facilitate the use of Internet to download and upload music files through the Internet without the permission of the owner of the rights, because of this, the music industry has tried to obtain a stronger legal protection. But the relation between this innovations and the industry seems to generating a new way of doing business. Despite of that, the music industry is still in a difficult situation, once the illegal trade of music online haven't stopped or diminished. Due to this music companies have been trying to develop a technological solution for this problem thought softwares to control the uses consumer can do of the music.